Developing A Superior Business Strategy Through Industrial Environment And Resources In Manufacturing Smes In West Java Province - Kania Agustina; Otong Karyono (Budapest International Research and Critics University, 2019)
Developing a superior business strategy in manufacturing Usaha Kecil dan Menengah (UKM) or Small and Medium-sized Enterprises (SMEs)is an important and fundamental instrument in answering the existing high competitiveness challenge. One of which is by implementing a business strategy that is adjusted tothe resources provision and the aspect of industrial environment to realise the superior business strategy. This research is a quantitative research with the analysis technique used is path analysis. The results of the analysis showed that the implementation of the business strategy is highly influenced by the industrial environmental factor and the resources provision owned by the manufacturing SMEs.